Sovintersport and the cashing in on Soviet football. (2nd January 2017) - Veth, K. Manuel
Abstract : This article focuses on the Soviet sports agency Sovintersport, which was created in the late 1980s and became an import–export company for everything related to sport in the Soviet Union. Sovintersport and its subsidiary companies were responsible for importing and exporting sporting equipment, negotiating sponsorship contracts with foreign companies, as well as the transferring of Soviet athletes and coaches to other countries. This article will, therefore, analyse the operations of Sovintersport and its subsidiary companies in the period between 1987 and 1991, with a special focus on foot-ball related operations. Sovintersport is in many ways is an excellent case study, which illustrates how international trading corporations that were set up during Gorbachev's reign of the Soviet Union, operated. Sovintersport demonstrates how football in the Soviet Union turned from a spectator sport into a valuable asset that was worth capitalizing on.